Helena Ramírez, Heidy Aguirre Guadamuz, Mónica Arce Oviedo. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 2025)
Grupo pequeño de personas
Colección Fototeca UNED
Keywords: Ramírez, Helena; Aguirre Guadamuz, Heidy; Arce Oviedo, Mónica; FOTOGRAFÍAS; UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA